The new model of lifelong learning in creating university's developmental potential - Monika Kłos; Małgorzata Burzyńska (Wydawnictwo Naukowe Uniwersytetu Mikołaja Kopernika, 2015)
The aim of the article is to outline the role of the university in planning and organizing lifelong learning, taking into consideration the perspective of the possibility of knowledge sharing, applied during the implementation of a project co-financed by the European Union within the European Social Fund. First, the authors draw the basic concepts of the project "PI: The new model of lifelong learning in creating university's developmental potential," implemented at the Higher School of Business in Pila. Second, they describe scientific conferences devoted to the innovative model of lifelong learning organized by four different institutions of higher education.